Performance of fingermillet (Eleusine coracana (L.) Gaertn) in association with different MPTs in agroforestry system - Anusha, S.; ., Nagaraju; Mallikarjuna, G.B.; Bhaskar, V.; Kombali, Gururaj; Vishwanath, B.R. (Indian Journal of Agroforestry, 2020)
Field experiment was conducted at Bengaluru during Kharif 2011 comprised of eight treatments, fingermillet in association with seven MPTs and fingermillet alone as control. Sole fingermillet recorded significantly higher grain (3257 kg ha-1) and straw yield (5865 kg ha-1), which was attributed to higher growth and yield attributes like leaf area (855.67cm2), number of productive tillers (6.17 hill-1), total dry matter (47.43 g hill-1), ear head weight (20.83 g hill-1), and grain yield (17.17 g hill-1). Fingermillet in association with Madhuca latifolia recorded higher grain (2838 kg ha-1) and straw (5104 kg ha-1) yield, whereas fingermillet with Melia dubia recorded significantly lower grain (1607 kg ha-1) and straw (2936 kg ha- 1) yield. Among the direction from tree row, southern side recorded significantly higher fingermillet grain (2555 kg ha-1) and straw (4547 kg ha-1) yield as compared to northern side. As distance increased from tree row, there was significant increase in fingermillet grain (2522 kg ha- 1) and straw (4501 kg ha-1) yield. Among the MPTs based agroforestry system, fingermillet in association with Melia dubia recorded higher net returns (42180 ha-1) and B: C ratio (3.96).